FASE KOMPRESI DI SELAT MAKASSAR BERDASARKAN DATA GEOLOGI DARATAN, SEISMIK LAUT DAN CITRA SATELIT - Bachri, Syaiful (Jurnal Geologi dan Sumberdaya Mineral, 2012)
Seismic data indicates that the last deformation period in the Makassar Strait has been undergonein compressional phase, different from the previous period as reported by many authors that Makassar Strait was formed in extensional phase. Terrestrial geology data obtained from West Sulawesi indicate that the vergence of thrust-fold belt is directed to the west, and is still active up to now. Meanwhile, the thrust and fold structures found in East Kalimantan have a vergence directed to the east. Seismic data from the eastern part of the Makassar strait shows that the youngest sediments is thrusted and folded with a vergence to the west. On the other hand, the youngest sediments from the western part of the strait is thrusted, folded and verging to the east. Meanwhile, the satellite imagery of the Makassar Strait shows that the west margin of West Sulawesi is similar to the margin of Paternoster Platform, suggesting an opening tectonics. However, interpretation of the youngest structures on the imagerry indicate that after opening episode subsequently was followed by compressional phase.Key words: compressional phase, extensional phase, Makassar Strait, thrust-fold belt, vergence.